Analysis of Factors Contributing to the Failure to Utilize the Public Health Center Information Management Systems (SIMPUS) at the Burneh Public Health Center - Daniyanti, Eka Suci; Eddy Moeljono; Fahmi, Muhammad Fikri (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
The optimal Public Health Center Information Management Systems (SIMPUS) aims to reduce workload and improve service efficiency   in Public Health Centers. However, the patient registration process at Burneh Public Health Center is still done manually due to the inability to use, the SIMPUS application after the computer is damaged and not promptly repaired.  This manual medical record storage system adversely affects patient service duration. The objective of this study is to identify the reasons for the failure of SIMPUS usage. The method employed is descriptive with a qualitative approach. Interviews and observations serve as the research instruments. The results indicates several factors contributing to the failure of SIMPUS usage, including inadequate human resources (lack of competence officers and insufficient knowledge), unmet budgetary support for SIMPUS usage, absence of Standard Operating Procedures (SOPs) for usage, and inadequate facilities, infrastructure, and equipment to support effective SIMPUS utilization. Addressing these issues   at Burneh Public Health Center can resolve challenges associated  with SIMPUS.